Technical and tactical performance of top-class senior, junior and cadet table tennis players - Malagoli Lanzoni, I.; Di Michele, R.; Merni, F. (International Journal of Table Tennis Sciences, 2013)
In the recent sports science literature, it is possible to notice that research branches related to performance analysis are widely developing [1]. The aim of this study was to analyze technical and tactical differences among male table tennis athletes of three categories: top-class world players (T), elite European juniors (J) and elite European cadets (C). 20 matches were randomly selected (T: 10, J: 5 and C: 5). Selected performance indicators were: stroke type, footwork type, and shot outcome. Selected matches have been watched in slow motion (0.2X) by an experienced table tennis coach, who collected the indicators of interest. The data were analyzed with the Excel software using contingency tables. The strokes most used by T were top forehand (19 %), top counter top forehand (16 %) and block backhand (14 %). A similar distribution was observed for J: top forehand (21 %), top counter top forehand (15 %) and block backhand (15 %). Conversely, C showed the top forehand as the most used stroke (22 %), followed however by the push forehand (16 %). Concerning the footwork type, the most used one was the one step (T: 32 %, J: 28 % and C: 31 %). Differences among groups were observed for the chassè (T: 24 %, J: 15 % and C: 15 %), and stroke without step (T: 18 %, J: 29 % and C: 28 %). Strong associations were observed between stroke and footwork types, and between stroke types and shot outcome, with the top forehand and top counter top forehand being the most successful strokes in all the groups. By studying the relationships between strokes, footwork types and shot outcomes in table tennis athletes of three different categories, it is possible to detect differences in the play style among the three categories of players. This analysis can help to improve the technical and the tactical skills of players to obtain better competitive results.